2021
DOI: 10.2147/ijwh.s284321
|View full text |Cite
|
Sign up to set email alerts
|

How Relevant is Obstetrician and Gynecologist Gender to Women in Saudi Arabia?

Abstract: Background:The patient-doctor relationship is one of the most important factors in determining the outcome of healthcare. The first step in establishing this relationship is choosing a physician. This study sought to identify patient preferences concerning the gender of their obstetrics and gynecology (OB-GYN) physician and the effect of religion and society on these choices. Methods: A cross-sectional study was conducted at the OB-GYN outpatient clinics at King Abdulaziz University Hospital in Jeddah between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Moreover, a majority of the participants preferred female OB-GYNs for major gynecological surgery. Similar results have been documented in two Saudi studies [ 12 , 14 ] conducted in Jeddah.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, a majority of the participants preferred female OB-GYNs for major gynecological surgery. Similar results have been documented in two Saudi studies [ 12 , 14 ] conducted in Jeddah.…”
Section: Discussionsupporting
confidence: 91%
“…The physician attitude and professionalism (45.6%), physician availability (29.2%), and female physician who is more patient and understanding (14.4%) were found in descending order of percentages. When comparing these results to similar previous studies, two studies, conducted in Jeddah [ 12 , 14 ], showed that the most affecting factors were knowledge and experience, board certification, and recommendation by relatives or friends. Although reputation is one of the important factors found in those two studies, physician reputation was the least selected factor in our study.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations